Գարեգին Սրվանձտյանցի բանահավաքչական ու ազգագրական գործունեությունը - Դեմիրճյան, Պետրոս (ՀՀ ԳԱԱ «Գիտություն» հրատ.)
Епископ Гарегин Срвандзтянц (1840–1892 гг.) – один из самых заслуженных представителей армянского народа – и как преданный национально-общественный деятель, и как несравненный филолог, собиратель фольклора и этнограф. Важнейшей частью его деятельности является серия сборников, являющихся результатом тщательного сбора в течение десятилетия (1874–1884 гг.) народных сказаний и преданий, богатых этнографических материалов. С именем Г. Срвандзтянца связано, в частности, выявление, записывание и публикация первого варианта армянского национального эпоса «Сасна црер» – «Давид Сасунский, или Дверь Мгера». За выполнение на высоком уровне вышеупомянутых масштабных работ, в филологии он считался основоположником армянского фольклора и этнографии. Также был оценен на международной арене, будучи избранным почетным членом Императорской археологической академии в Санкт-Петербурге․ Bishop Garegin Srvandztyants (1840–1892) is one of the most merited representatives of the Armenian people, both as a devoted national-public figure and as an incomparable philologist, folklore collector and ethnographer. The most important part of his activity is a series of collections, which are the result of a diligent collection оf over a decade (1874–1884) of folk tales and traditions and wealthy ethnographic materials. The name of G. Srvandztyants is associated, in particular, with the identification, recording and publication of the first version of the Armenian national epic “Sasna Tsrer” – “David of Sassoun or Mher’s Door”. For the high-level performance of the abovementioned large-scale works, he was considered the founder of Armenian folklore and ethnography in philology. He was also evaluated in the international arena, being elected an honorary member of the Imperial Archaeological Academy in St. Petersburg.
Keywords: Բանասիրություն